Psychological Well being of elected Female Representatives in India - Kaur, Gurpreet (Innovative Research Thoughts, 2017)
Women's responsibilities are evolving in new ways today, as they demonstrate a new level of dedication to both their professional lives and their families. As a result, working women experience an increased level of anxiety and tension. Women working nowadays may be observed all throughout the world, not only in India. Increasingly, the government is providing possibilities for women's education, awareness, and advancement. As a result, more and more women are taking use of these resources. Slowly, but surely, they're gaining ground on males in all walks of life. In addition to their employment duties, working women are also moms, instructors, carers for their ageing parents, and more, all of which may be quite taxing on their time and energy. In working women with small children, the increased load and duty of housework contribute to everyday inconveniences or stress, which has a significant impact on their psychological well-being. Many studies on the subject of work-family conflict are predicated on the notion that taking on numerous responsibilities leads to stress.